Enhancing Female Students' Classroom Participation in Economics to Improve Academic Performance: A Case Study of 12th-Grade Social Science Students at Shaleka-Jateni Secondary School - Kasahun, Melion; Hailemariam, Getachew; Tadele, Tihitina; Duba, Obsitu; Lemma, Tesfaye; Kore, Burje (International Journal of Advance Research in Education & Literature (ISSN 2208-2441), 2025)
This study investigates the classroom participation of female students in Economics and its impact on academic performance at Shaleka-Jateni Secondary School, Yabello Town, Borana Zone, Oromia Regional State, Ethiopia. Data were collected through classroom observations, interviews, Focus Group Discussion (FGD), surveys, and academic assessments. Findings reveal that female students face significant barriers to active engagement due to socio-cultural norms, institutional factors, and psychological challenges, leading to lower participation levels compared to their male counterparts. Classroom observations, surveys, and teacher interviews indicate that only 17.8% of female students actively participate in discussions, while 75.6% hesitate to ask questions. Gender bias, lack of confidence, and fear of judgment further discourage engagement. However, targeted interventions—such as interactive teaching, collaborative learning, teacher support, relatable content, and the presence of female role models—led to notable improvements. Post-intervention assessments show a 37% increase in classroom participation and significant gains in academic performance, Written test scores improved by 27%, oral presentations by 23%, and overall classroom participation by 37%. Correlation analysis confirms that enhanced participation positively impacts academic outcomes. These findings highlight the importance of gender-inclusive teaching strategies in bridging the participation gap and improving female students' academic performance. Sustained institutional support, teacher training, and mentorship programs are essential to fostering an equitable learning environment. The study also suggests the need for further research on the long-term effects of such interventions and their applicability in other educational contexts.